Antianxiety effect of vinpocetine on caffeine-induced anxiety in rats - Mahmood, Farah Mohammed Najeeb (Kulliyyah of Pharmacy, Internatonal Islamic University Malaysia, 2018)
Anxiety disorders (AD) are increasing in all societies, especially developed ones. Caffeine (CAF) consumption in coffee, tea, and other beverages may aggravate and increase the frequency of anxiety symptoms. Vinpocetine (VP) is a synthetic derivative of the lesser periwinkle plant alkaloid vincamine and is used as a neuroprotective agent. The study was conducted to evaluate the capacity of VP to alleviate anxiety symptoms and to compare its effectiveness to that of lorazepam (LZP). The anxiety model in rat was induced via CAF injection (i.p.). Behavioural evaluation of the anxiety level in animal groups with and without treatment (oral LZP and VP) after a period of one month of treatment was done through elevated plus maze (EPM) apparatus. Additionally, neurochemical assessment of CAF, VP and LZP effects on rat brain neurotransmitters were done by using Ultra-performance liquid chromatography (UPLC). The results demonstrated the anxiogenic action of caﬀeine in rats receiving a high dose of CAF (100 mg/kg), as indicated by a significant increase (p < 0.001 ): in the number of entries (29 ± 5.5) and the duration of stay (292 ± 67) in the closed arms of the EPM compared to CONT group (4 ± 1.4) and (22 ± 5), respectively. After 30 days of treatment, VP led to anxiolytic effects in EPM behaviour. A pronounced anxiolytic effect was observed in rats administered with different doses of VP (10 mg [VP1], 20 mg [VP2] and 30 mg [VP3] /kg/day; p.o.), as compared to CONT and LZP groups. The concentration of serotonin (5-HT) in cingulate gyrus of VP2 (5.45 ± 0.05), VP3 (6.06 ± 0.02) and LZP (5.1 ± 0.01) groups was significantly decreased (p < 0.001) compared to the CAF group (9.45 ± 0.18) which may indicate that the VP at moderate and high doses has a negative correlation with the concentration of 5-HT and acts as anxiolytic agent. In the hippocampus, VP has significantly increased GABA concentration in VP1 (1010.14 ± 9.4), VP3 (1043.92 ± 18.73) and LZP (1093 ± 3.35) compared to CAF group (910.56 ± 18.32, p < 0.01). The concentrations of EPI in VP2 (8.64 ± 0.79) & LZP (8.41 ± 0.03) in frontal cortex were significantly decreased (p < 0.001) compared to the CAF group (10.33 ± 0.03), which may explain the anxiolytic effects of VP and LZP on a behavioural study. On the basis of the results obtained in the present study, it is concluded that long-term administration of VP at different doses presented anxiolytic-like activity on EPM test at least via 5-HT, GABA and EPI.